PENERAPAN MEDIA COUNTING BOX (KOTAK BERHITUNG) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - repni, repni; Efendi, Rinja; Siregar, Pariang Sonang (Jurnal Dikdas Bantara, 2022)
This study aims to improve the learning outcomes of grade one students at Al-Muflihun Islamic Elementary School by applying the Counting Box media. The subjects of this research are students the first grade of Al Muflihun Islamic Elementary School, totaling 31 students, with 18 boys and 13 girls .The type of research used is Classroom Action Research (CAR).which consists of 2 cycles, each cycle consists of 2 meetings. The data collecting technique were used  observation and written tests. Based on research results it can be concluded that in the first cycle of the student learning outcomes completeness 77.5% with class average is 77.7 and has not yet reached the 80% success indicator. Completeness of results student learning in the second cycle is 93.6% with a class average of 89.03 and reachesindicator of success that has exceeded 80%. Thus it can be concluded that with the application of Counting Box media can improve student learning outcomes first grade at Al Muflihun Islamic Elementary School on addition and subtraction mathematics numbers 1-50.